The role of transvaginal ultrasound in assessing ovarian function and guiding treatment in infertility management - Babita; Dev, Kapil (International Journal of Research in Medical Sciences, 2025)
This study investigates the role of transvaginal sonography (TVS) in diagnosing and managing female infertility. It highlights TVS's effectiveness in detecting ovulatory disorders, structural abnormalities and age-related fertility issues. Results revealed 85% accuracy in diagnosing polycystic ovary syndrome (PCOS) and a 92% accuracy in identifying uterine anomalies, significantly aiding treatment planning. TVS also contributed to the evaluation of endometrial issues and ovarian reserve in women over 35, revealing diminished reserves in 68% of cases. Compared to hysterosalpingography (HSG) and laparoscopy, TVS offered a non-invasive, cost-effective and comfortable alternative for structural evaluations. The findings underscore the value of TVS in personalizing fertility treatments, particularly in assisted reproductive technologies (ART).